KOMUNIKASI PENGUNGKAPAN DIRI PENGGUNA ROKOK ELEKTRONIK DI KALANGAN MAHASISWA - Surachman, Akhmad Yani; Ardiansyah, Geri; Sonjaya, Soni (PRoListik : Jurnal Ilmu Komunikasi, 2023)
Individuals who are in a new environment will adapt to that environment by self-disclosure. When an individual tries to express himself, the stages of the process in question will proceed from the outermost layer of the person's self and will take him to a closer layer of relationships, and vice versa. So that in the end it will produce a reciprocal relationship between fellow electronic cigarette users. This research aims to determine the process of self-disclosure of electronic cigarette users to fellow electronic cigarette users; reciprocal relationships formed as a result of self-disclosure of electronic cigarette users; the level of closeness of a person in communicating using the concept of "self-disclosure" towards other electronic cigarette users using a phenomenological approach. The research results show that opening up begins with sharing about the world of vaping and then moving on to other discussions, including personal problems. Self-disclosure in a group does not occur well because it only occurs on the surface or only as a driving force towards relationship development. The level of closeness a person has in communicating using the concept of "self-disclosure" towards other electronic cigarette users occurs at the level of members' interpersonal relationships, not at the overall level as members of a group.